A case report of colon interposition radical surgery performed via unilateral thoracotomy in a patient with esophageal cancer after billroth II gastrectomy - Wang, Chun-Guang; Zhang, Guang-Xin; Zhang, Yan; Guo, Hang; Zhang, Guang-Lei; Kang, Zhen-Hua (Frontiers in Oncology, 2024)
IntroductionWhen a gastric tube cannot be used as a substitute for the esophagus, the colon offers several advantageous features for esophageal replacement. However, this procedure remains complex and necessitates patients to have a favorable nutritional status. In this study, we investigated the viability of intrathoracic colonic interposition anastomosis through a single thoracic incision, with the goal of mitigating surgical challenges and nutritional requirements.Case descriptionWe conducted a colectomy and reconstructed the esophageal-colonic-gastric tract via the esophageal bed into the left thoracic cavity for a 68-year-old male patient with compromised nutritional status following 30 years post-Billroth II (BII) gastrectomy. Under normal circumstances, this patient would not have been deemed an appropriate candidate for a conventional colonic interposition procedure. The patient resumed a soft diet through the normal digestive tract two weeks after the surgery and was discharged 20 days later.ConclusionPatients who have previously received a Billroth II Gastrectomy and subsequently developed early-stage esophageal cancer, characterized by the absence of lymph node metastasis, are suitable candidates for Colon Interposition Radical Surgery via left thoracotomy.